NUTRITIONAL INTERVENTION USING CHICKEN EGGS AND ZINC TO ENHANCE GROWTH IN STUNTED CHILDREN AGED 6–72 MONTHS - Rizkiana Putri; Gaidha Khusnul Pangestu (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2026)
The results of the 2023 Indonesian Health Survey showed that the prevalence of stunting and wasting in toddlers was 21.5% and 8.5%. The stunting rate in Central Java Province was 20.7%, while wasting was 7.1%. Toddlers who experience growth retardation as a result of poor nutritional intake or repeated infections have a high risk of death and illness. This study aims to determine the effect of providing chicken eggs and zinc to improve growth of children with stunting. The study used Quase-Experiment one group pre-posttest design with 30 respondent for 90 days of intervention. The results showed that 86.67% of toddlers were stunted and 13.33% were severely stunted. The analysis test showed a significant difference and there was an effect of providing chicken eggs and zinc on increasing toddler weight (p-value 0.00). Likewise, for height, the p-value was 0.00, indicating that there was an effect of providing chicken eggs and zinc on increasing toddler height. Providing chicken eggs and zinc can be considered as an intervention to improve toddler nutritional status.